Molecular mechanisms of protein-bound uremic toxin-mediated cardiac, renal and vascular effects: underpinning intracellular targets for cardiorenal syndrome therapy. (15th June 2019) - Savira, Feby; Magaye, Ruth; Hua, Yue; Liew, Danny; Kaye, David; Marwick, Tom; Wang, Bing Hui
Highlights: There is an abundance of mechanistic studies involving the multi-organ effect of PBUTs. We gathered evidence on molecular mechanisms in PBUT-mediated cardiac, renal and vascular effect. Potential therapeutic targets to block PBUT adverse effects in the CRS setting based on mechanistic studies are also outlined. Abstract: Cardiorenal syndrome (CRS) remains a global health burden with a lack of definitive and effective treatment. Protein-bound uremic toxin (PBUT) overload has been identified as a non-traditional risk factor for cardiac, renal and vascular dysfunction due to significant albumin-binding properties, rendering these solutes non-dialyzable upon the state of irreversible kidney dysfunction. Although limited, experimental studies have investigated possible mechanisms in PBUT-mediated cardiac, renal and vascular effects. The ultimate aim is to identify relevant and efficacious targets that may translate beneficial outcomes in disease models and eventually in the clinic. This review will expand on detailed knowledge on mechanisms involved in detrimental effects of PBUT, specifically affecting the heart, kidney and vasculature, and explore potential effective intracellular targets to abolish their effects in CRS initiation and/or progression.